ANALYSIS OF FINANCIAL DISTRESS IN BROADCASTING SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Febinda; Zainal Ruma; Anwar; Andi Mustika Amin; Anwar Ramli (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
Financial distress, also known as financial difficulties, refers to a situation in which a company experiences unhealthy financial conditions or a crisis. It typically starts with increasing liquidity pressure and continues with a decrease in the value of company assets, ultimately leading to bankruptcy. Bankruptcy poses a significant risk for companies; however, this risk can be minimized or prevented through the use of bankruptcy detection models or tools. The purpose of this study was to assess the financial distress of companies in the Broadcasting Sub-Sector listed on the Indonesia Stock Exchange during the period of 2017-2021. The Springate, Zmijewski, and Grover models were employed for this analysis. The study's population comprised companies in the Broadcasting Sub-Sector listed on the Indonesia Stock Exchange during the specified period, amounting to 5 companies. A research sample of 4 companies was selected using a purposive sampling technique. The findings indicate that according to the Springate model, two companies, namely PT. MDIA Tbk with a rate of 80% and PT. VIVA Tbk with a level of 100%, were in a state of financial distress. The Zmijewski model identified PT VIVA Tbk as the only company in financial distress with a level of 80%. Additionally, based on the Grover model, PT. VIVA Tbk exhibited a financial distress level of 40%.